Toward a Value-Based Digital Religious Literacy Framework: Contextualizing Akidah-Akhlak in the Digital Era - Miftahul Jumaidah; Adiyono Adiyono; Niswatun Zahra (Nuris Journal of Education and Islamic Studies, 2026)
The development of digital technology presents serious challenges in Islamic education, particularly related to students' low digital religious literacy skills in filtering religious information in digital media. The teaching of creeds and morals tends to be normative and lacks contextualization, creating a gap between the understanding of Islamic values ​​and religious practices in the digital space. This study aims to analyze the contextualization strategy of creed and moral values ​​in shaping students' digital religious literacy at the Paser State Islamic Senior High School (MAN). The study used a descriptive qualitative approach with a case study design, using observation techniques, in-depth interviews, and documentation with teachers, the principal, and students. The results show that the contextualization of creed and moral values ​​encompasses three main dimensions: meaningful learning based on students' digital experiences, strengthening digital competencies based on Islamic ethics, and developing critical awareness of digital content. The implementation strategy was carried out through interactive digital media, case-based discussions, and digital spiritual reflection. These findings confirm that the integration of creed and moral values ​​with digital literacy contributes to improving students' Islamic understanding, moral responsibility, and religious moderation in the digital era.